The effect of online customer review and perceived risk on purchase decisions: A study of Somethinc consumers on the TikTok shop platform - Syafrina, Mia; Asyifa, Pramitha; Firdaus, Fadli; Sudarso, Dian Mulyaningtyas; Mulyana, Andi Erna (Pusat P2M Politeknik Negeri Batam, 2026)
This study analyzes the effects of online customer reviews and perceived risk on Somethinc consumers’ purchase decisions on TikTok Shop in Batam. A quantitative survey was conducted with 100 Generation Z respondents aged 15–24 years who had previously purchased Somethinc through TikTok Shop. Data were collected using a 4-point Likert questionnaire distributed via Google Forms and analyzed with multiple linear regression. The results show that online customer reviews have a positive and statistically significant effect on purchase decisions, while perceived risk has a negative but insignificant effect. Together, the two variables explain 36.8% of the variance in purchase decisions. These findings highlight the strategic role of user-generated reviews in shaping Gen Z consumers’ purchasing behavior and suggest that perceived risk may be less salient for a well-known local beauty brand operating on a popular social commerce platform.